Desenvolvimento e caracterização de novas formas sólidas multicomponentes do cloridrato de ondansetrona e ricobendazol - Silva, Keilla Façanha (2022)
The therapeutic efficacy of drugs is directly related to their physicochemical characteristics, which, in turn, are linked to the structural arrangement they present. They are derived from the different conformations and intramolecular and intermolecular interactions that define the crystalline packing of molecules in different solid forms. The objective of the present work was to develop multicomponent solids for the active pharmaceutical ingredients (APIs) ondansetron hydrochloride (ODT) and ricobendazole (RBZ). For this, crystal engineering strategies were adopted, combining the functional groups of APIs with functional groups of coformers, which formed supramolecular synthons by intermolecular hydrogen interactions. Ondansetron hydrochloride is a drug administered to control side effects induced by the cytotoxic character in chemotherapy and radiotherapy treatments. It has high aqueous solubility, but producing a cocrystal with low solubility may be an option for a slow and sustained release of the active ingredient. For this compound, we obtained four new structures. Ricobendazole is a drug widely used to prevent and treat parasitic diseases. It has low aqueous solubility causing low bioavailability, which motivated us to search for new structures such as cocrystals and salts. The preparation methods induced the formation of five new crystal structures. In addition, we elucidate and characterize its crystalline structure since no structural information is reported in the literature. The methods applied to obtain the new solid forms were mechanochemical activation, slurry, and slow evaporation of the solvent. Single crystal X-ray diffraction was used for structural elucidation, while characterization was performed by powder X-ray diffraction, vibrational spectroscopy in the infrared region, and thermal analysis by thermogravimetry and differential scanning calorimetry techniques. The solubility test was also performed, aiming to compare the profile of the new solid forms with the commercially available form.